A generalization of a contraction principle in probabilistic metric spaces. Part II - Dorel Miheţ (International Journal of Mathematics and Mathematical Sciences)
A fixed point theorem concerning probabilistic contractions satisfying an implicit relation, which generalizes a well-known result of Hadžić, is proved.